(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
As a result of a comprehensive assessment of the natural conditions of the Rostov Region, areas were identified that are most favorable for the development of specially protected natural areas. An assessment was made of the current state of these areas in terms of the diversity of plant community species, the extent of arable land, and the forest cover of the area.